Pengaruh kompres air hangat memakai jahe untuk menurunkan skala nyeri pada lansia dengan gout artritis - Avilia, Devi; Sutrisno, Sutrisno; Agista, Setia; Wati, Yuni Panca (Universitas Aisyah Pringsewu (UAP) Lampung, 2020)
Gout Arthritis is one of the most common inflammatory joint disease that is characterized by a buildup of monosodium urate crystals in or around the joints, causing swollen pain in the joints. Management of this pain is done by using warm water compress therapy using ginger aiming to reduce pain in the joints.The goal is to analyze the results of the implementation of community nursing care by giving warm water compresses using ginger to the elderly to meet pain needs. The method in writing Scientific Papers is a case study taken in RT 09 Margabatin Village, East Lampung, with 10 respondents. Results intervention carried out for 3x 60 minutes by giving warm water compresses using ginger is obtainedthat the average pain scale before applying warm water compresses using ginger is 4 (moderate pain), after a warm water compress is done using ginger is 2 (mild pain). So it can be concluded that there is an effect of giving warm.